Catálogo florístico del Macizo de Líbar (Parques naturales Sierra de Grazalema y Los Alcornocales, Málaga-Cádiz, España) - Becerra Parra, M.; Robles Domínguez, E. (Acta Botanica Malacitana, 2007)
The Mountain of Líbar is one of the most important ranges of the mountainous area of Ronda and Western Andalusia. Its main orographic characteristic is the presence of two mountainous alignments that delimit a great intramountainous depression denominated Llanos de Líbar. The Quercus rotundifolia wood is the main vegetation in limestone lands, whereas the Q. suber forest is dominant in sandstone zones. Other plants communities present in this area are dominated by Q. faginea, Olea europaea, Ceratonia siliqua, Fraxinus angustifolia, Ulmus minor, Nerium oleander and other shrublands. This is one of the zones with highest rainfall in the Iberian Peninsula and with mild temperatures, although in the summits, the annual average temperature, decreases near 10 ºC. In order to carry out the botanical study, samplings have been made during five years, in addition to a bibliographical revision and review of biodiversity databases. The botanical catalogue of Líbar is composed by 826 species, 128 are endemic species with different distribution area. Linaria platycalyx, Reseda gayana subsp. undata or Saxifraga bourgeana are endemic from the area of Ronda. 13 species are protected according to the Law of Wild Flora and Fauna of Andalusia and 32 species are included in the plants Red List of Andalusia.
Keywords: Cádiz.; Catalogue; Flora; Los Alcornocales; Macizo de Líbar; Málaga; Sierra de Grazalema